Axillary lymph node dissection versus sentinel lymph node biopsy alone for early breast cancer with sentinel node metastasis: A meta-analysis. Issue 8 (August 2015) - Li, C.Z.; Zhang, P.; Li, R.W.; Wu, C.T.; Zhang, X.P.; Zhu, H.C.
Abstract Background In early breast cancer patients with sentinel node metastasis, the effect of axillary lymph node dissection (ALND) is controversial. The purpose of this study is to compare the safety and efficacy of sentinel lymph node biopsy (SLNB) alone versus ALND in patients with early breast cancer and sentinel node metastasis. Methods We searched PubMed, Embase, Web of Science, and Cochrane Library databases from 1965 to February 2014. All data were analyzed using Review Manager Software 5.2. Results 12 studies, which included 130, 575 patients from five randomized controlled trials and seven observational studies, met our inclusion criteria. 26, 870 early breast cancer patients underwent SLNB alone and 103, 705 underwent ALND. Patients underwent ALND had more paresthesia (risk ratio [RR] 0.26, 95% confidence interval [CI] 0.20–0.33; p < 0.01) and lymphedema (RR 0.28, 95% CI 0.20–0.41; p < 0.01) than those had SLNB alone. There were no significant differences in overall survival (hazard ratio [HR] 0.95, 95% CI 0.85–1.06; p = 0.35), disease-free survival (HR 1.00, 95% CI 0.98–1.02, p = 0.96), and locoregional recurrence (RR 0.92, 95% CI 0.59–1.44; p = 0.73). Conclusion Current evidence indicates that axillary dissection may be omitted in early breast cancer patients with sentinel lymph metastasis.